2017
DOI: 10.1108/imds-06-2016-0245
|View full text |Cite
|
Sign up to set email alerts
|

Three-level supply chain coordination of fresh agricultural products in the Internet of Things

Abstract: Purpose-The Internet of Things (IoT) is used in the fresh agricultural product (FAP) supply chain, which can be coordinated through a revenue-sharing contract. The purpose of this paper is to make the three-level supply chain coordinate in IoT by considering the influence of FAP on market demand and costs of controlling freshness on the road. Design/methodology/approach-A three-level FAP supply chain that comprises a manufacturer, distributor, and retailer in IoT is regarded as the research object. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 37 publications
0
41
0
4
Order By: Relevance
“…Similar to Ma et al, there are many studies adopting the "cost + revenue sharing" contract [9]- [14]. In addition, buyback contract [15], price subsidy contract [16] and risk compensation contract [11] are relatively common. Different from the above literature, Moon et al find that compared with revenue sharing and cost sharing contracts, an incremental quantity discount contract is more effective for the coordination of fresh food supply chain with fairness concern [17]; Mohammadi et al propose a joint contract for "revenue sharing" and "fresh-keeping technology sharing" [18].…”
Section: A Fresh Supply Chainmentioning
confidence: 99%
“…Similar to Ma et al, there are many studies adopting the "cost + revenue sharing" contract [9]- [14]. In addition, buyback contract [15], price subsidy contract [16] and risk compensation contract [11] are relatively common. Different from the above literature, Moon et al find that compared with revenue sharing and cost sharing contracts, an incremental quantity discount contract is more effective for the coordination of fresh food supply chain with fairness concern [17]; Mohammadi et al propose a joint contract for "revenue sharing" and "fresh-keeping technology sharing" [18].…”
Section: A Fresh Supply Chainmentioning
confidence: 99%
“…On the basis of the characteristics of perishable foods, Zheng et al [46] designed a fresh food supply chain (FPSC), taking the cost of freshness preservation into account, and the results showed that fresh-keeping cost-sharing and the revenue-sharing contract has the best coordination effect on FPSC. Taking the field of Internet of Things as a research object, Yan et al [47] improved the revenue-sharing contract for the fresh agriculture supply chain to discuss the impact of fresh agricultural products on costs of controlling freshness and market demand. Obviously, the above studies have well documented the motivation of agriculture to use revenue-sharing contracts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To the best of our knowledge, disruption occurrence regarding the collection process, which is a significant issue in both theory and practice, has not been studied in the literature. Coordination plans are good means of improving the supply chain profitability ( Hosseini-Motlagh et al, 2018 ) and balance the including parties’ conflict of interests ( Yan et al, 2017 ). Therefore, many papers utilize this approach to manage disruptions in production systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Competition aggravates the conflict of interests between parties and adversely affects the profitability of the whole chain, which can be neutralized by an appropriate coordination scheme ( Yan, 2011 ). This is because coordination mechanisms effectively improve the chain’s profitability ( Hosseini-Motlagh et al, 2018 ) and balance the members' conflict of interests ( Yan et al, 2017 ). Various coordination strategies are widely applied in real businesses, such as IBM, Sun Microsystems, and Hewlett Packard ( Heydari et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%